Assessing the professional identity of primary student teachers: Design and validation of the Teacher Identity Measurement Scale. (March 2020) - Hanna, Fadie; Oostdam, Ron; Severiens, Sabine E.; Zijlstra, Bonne J.H.
Highlights: We developed a purely quantitative instrument for measuring teacher identity. Teacher identity is considered as a second-order construct. Teacher identity was decomposed in four first-order constructs. These constructs are: motivation, self-image, self-efficacy, and task perception. qualitative and quantitative scale development approaches were used. Abstract: This study aimed to design and validate the Teacher Identity Measurement Scale (TIMS) for assessing primary student teachers' professional identity. Based on identity theory and a systematic review into quantitative instruments of teacher identity, teacher identity was decomposed in four first-order constructs: motivation, self-image, self-efficacy, and task perception. This resulted in a measurement scale consisting of 46 items. The factorial design was examined by administering the TIMS to first- and second-year primary student teachers. In phase 1, involving 17 students, qualitative scale development methods were used to assess the construct validity. In phase 2, its second-order factor structure was tested and confirmed among a sample of 211 students. In phase 3, this structure was cross-validated among a new sample of 419 students. The instrument may contribute to understanding primary student teacher's professional development and can be used as a tool to support the process of developing a professional teacher identity.